2004
DOI: 10.1002/hep.20428
|View full text |Cite
|
Sign up to set email alerts
|

Opioid receptor blockade reduces Fas-induced hepatitis in mice

Abstract: Fas (CD95)-induced hepatocyte apoptosis and cytotoxic activity of neutrophils infiltrating the injured liver are two major events leading to hepatitis. Because it has been reported that opioids, via a direct interaction, sensitize splenocytes to Fas-mediated apoptosis by upregulating Fas messenger RNA (mRNA) and modulated neutrophil activity, we assumed that opioids may participate in the pathophysiology of hepatitis. Using the hepatitis model induced by agonistic anti-Fas antibody in mice, we showed that opio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…Unlike cardiomyocytes, hepatocellular protection by morphine was not associated with opioid receptors. Recent report showed that the liver is lack of opioid receptors [21], which is consistent with our results. The absence of opioid receptors in the liver may also explain why the dose of morphine for hepatocellular protection (50 μM) was higher than that required for protecting cardiomyocytes (1 μM) in which delta-and kappa-opioid receptors play a major role [22].…”
Section: Discussionsupporting
confidence: 94%
“…Unlike cardiomyocytes, hepatocellular protection by morphine was not associated with opioid receptors. Recent report showed that the liver is lack of opioid receptors [21], which is consistent with our results. The absence of opioid receptors in the liver may also explain why the dose of morphine for hepatocellular protection (50 μM) was higher than that required for protecting cardiomyocytes (1 μM) in which delta-and kappa-opioid receptors play a major role [22].…”
Section: Discussionsupporting
confidence: 94%
“…A brain site of opioid action is suspected (24,39,40). As an alternative, a direct peripheral action might be considered, although the presence of the MOR in liver and skeletal muscle remains poorly documented (41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Jaume and his colleagues reported that naltrexone reduces Fas-induced hepatitis in mice (48) and that opioid receptor antagonist improves the resistance of mice to Fas-induced hepatitis via a peripheral mechanism that does not involve a downmodulation of Fas mRNA in hepatocytes nor a decrease in pro-inflammatory activity of neutrophils. As mentioned in the previous discussions that liver damage has been associated with overproduction of ROS (1 -6) or TNF-α (15 -17, 34 -42), these publications lend support to our current results and our earlier report indicated that naltrexone is capable of preventing and / or protecting against LPS or LPS / D-gal-induced liver damage via modulation of ROS or TNF-α (18).…”
Section: Discussionmentioning
confidence: 99%